Fluoxetine protects against IL-1β-induced neuronal apoptosis via downregulation of p53. (August 2016) - Shan, Han; Bian, Yaqi; Shu, Zhaoma; Zhang, Linxia; Zhu, Jialei; Ding, Jianhua; Lu, Ming; Xiao, Ming; Hu, Gang
Abstract: Fluoxetine, a selective serotonin reuptake inhibitor, exerts neuroprotective effects in a variety of neurological diseases including stroke, but the underlying mechanism remains obscure. In the present study, we addressed the molecular events in fluoxetine against ischemia/reperfusion-induced acute neuronal injury and inflammation-induced neuronal apoptosis. We showed that treatment of fluoxetine (40 mg/kg, i.p.) with twice injections at 1 h and 12 h after transient middle cerebral artery occlusion (tMCAO) respectively alleviated neurological deficits and neuronal apoptosis in a mouse ischemic stroke model, accompanied by inhibiting interleukin-1β (IL-1β), Bax and p53 expression and upregulating anti-apoptotic protein Bcl-2 level. We next mimicked neuroinflammation in ischemic stroke with IL-1β in primary cultured cortical neurons and found that pretreatment with fluoxetine (1 μM) prevented IL-1β-induced neuronal apoptosis and upregulation of p53 expression. Furthermore, we demonstrated that p53 overexpression in N2a cell line abolished the anti-apoptotic effect of fluoxetine, indicating that p53 downregulation is required for the protective role of fluoxetine in IL-1β-induced neuronal apoptosis. Fluoxetine downregulating p53 expression could be mimicked by SB203580, a specific inhibitor of p38, but blocked by anisomycin, a p38 activator. Collectively, our findings have revealed that fluoxetine protects against IL-1β-induced neuronal apoptosis via p38-p53 dependent pathway, which give us an insight into the potential of fluoxetine in terms of opening up novel therapeutic avenues for neurological diseases including stroke. Highlights: Fluoxetine alleviated neuronal injury and p53 increase in a mouse model of tMCAO. Fluoxetine attenuated IL-1β-induced apoptosis and p53 elevation in cortical neurons. Downregulation of p53 was required for the neuroprotective effects of fluoxetine. Fluoxetine down-regulated p53 expression via a p38-dependent pathway.